RECOVERING BALANCE EQUITY LOSS OF COOPERATIVE: CASE OF K3PC - Haroen, Armis (JURNAL DARMA AGUNG, 2022)
In financial report capital structure, there is component equity. Equity consists of funds provided by the firm's owners (investors or stocks holders) that are repaid subject to the firm's performance (Lawrence J Gitman; Chad J Zutter (2009)). It means net capital in balanced component, as a balancing liability compared to assets. Equity describes how Firms or Corporations show their financial performance. Equity consists of paid-up capital, retained earnings, and business reserves. In the case of K3PC, Equity shows a loss compared to common (issued) stock equity to stockholders' equity. By the data report 2022, there is a gap of -4,16 billion rupiahs, even though it had already decreased from the data report 2021. It comes from the accumulative profit-loss statement for the period 2016 to 2019. Approaching historical data, balanced sheet and income statements were then formulated by Du-Pont analysis to get some financial ratios. The ratios measure the outcome of proforma financial planning that is produced to guide K3PC management when treating budget or forecast to recover and balanced the equity loss of K3PC. The innitiative plan of this research is to attack or maintain operating costs and paralelly develop a business strategy to get additional revenue from some of the K3PC unit business. Three scenarios are provided: the first one, as the current scenario, is described by nature as organic growth, and the second scenario provides to improve operating costs. It generates additional revenue by 10-20 % from the unit businesses. The third one was executed by technical aspects on K3PC AD-ART, designing the business reserved allocation till 30 % on the financial report. Hopefully, there are better opportunities and chances to accelerate equity loss recovery on the K3PC final report then still using relevant financial ratios.